2017
DOI: 10.1007/s11356-017-0232-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diosmin on aflatoxin-induced liver and kidney damage

Abstract: Aflatoxin is among the natural toxins that cause serious side effects on living things. Diosmin is also one of the compounds with broad pharmacological effects. In this study, the effects on the oxidant/antioxidant system of 50 mg/kg body weight/day dose of diosmin, aflatoxin (500 μg/kg body weight/day), and combined aflatoxin (500 μg/kg body weight/day) plus diosmin (50 mg/kg body weight/day) given to the stomach via catheter female adult Wistar Albino rats is examined. Forty rats were used in the experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 72 publications
6
18
0
Order By: Relevance
“…These findings were in line with those of Eraslan et al [44] and Zabad et al [45]. This may be attributed to hyperglycemia and/or AFB 1 -induced ROS leading to necrosis of proximal tubular epithelial cells [44,45]. To confirm the role of MD and AFB 1 -induced oxidative stress in disturbance of hepatorenal function, our study revealed that DM and/or…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings were in line with those of Eraslan et al [44] and Zabad et al [45]. This may be attributed to hyperglycemia and/or AFB 1 -induced ROS leading to necrosis of proximal tubular epithelial cells [44,45]. To confirm the role of MD and AFB 1 -induced oxidative stress in disturbance of hepatorenal function, our study revealed that DM and/or…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, injection of rats with STZ and/or AFB 1 significantly increased serum levels of urea and creatinine. These findings were in line with those of Eraslan et al [44] and Zabad et al [45]. This may be attributed to hyperglycemia and/or AFB 1 -induced ROS leading to necrosis of proximal tubular epithelial cells [44,45].…”
Section: Discussionsupporting
confidence: 91%
“…No significant difference/observance between the control group and diosmin‐alone group in term of oxidative stress parameter (MDA, NO, SOD, CAT, GSH‐Px, and GSH), biochemical parameters (AST, ALT, ALP, and LDH), histological architecture, body weight, liver weight, and liver weight/body weight ratio ascertained that diosmin did not cause negative effect at the specified dose and duration examined. Findings from diosmin administered at different doses and times, the parameters of oxidative stress (Arab et al, ; Eraslan et al, ; Rehman et al, ; Sharmila Queenthy, Stanely Mainzen Prince, & John, ), biochemical parameters (Eraslan et al, ; Sharmila Queenthy et al, ), liver histology (Eraslan et al, ; Rehman et al, ) findings obtained from this study are consistent with the findings obtained.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, diosmin/diosmetin also has a protective effect against peroxidation by inhibiting the oxidation of cell membrane phospholipids (Villa et al, ). When the previously performed studies involving different compounds with diosmin were evaluated, the oxidative stress parameters (Arab et al, ; Eraslan et al, ; Jain et al, ; Sharmila Queenthy et al, ; Srinivasan & Pari, ; Tahir et al, ; Wojnar, Kaczmarczyk‐Sedlak, & Zych, ), some biochemical parameters (Eraslan et al, ; Sharmila Queenthy et al, ; Tahir et al, ), and liver histopathology (Eraslan et al, ; Rehman et al, ; Srinivasan & Pari, ; Tahir et al, ) similar to those found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation